Histopathological Study of Tumor and Tumor Like Lesions of the Oral Cavity - Halder, Babai; Halder, Nirvana Rasaily (Annals of Pathology and Laboratory Medicine, 2019)
Background: The oral cavity is one of the most common site for various tumor and tumor like lesions. Development of oral cavity lesions are strongly linked with smoking. Hemangioma is the commonest benign tumor. Inflammatory fibrous hyperplasia is the commonest non-neoplastic reactive lesion. Squamous cell carcinoma (SCC) is most common among malignant lesions. Aims & Objectives: To study the histopathological patterns & variations of oral cavity lesions. Materials and methods: A three year retrospective cross-sectional study by histopathological examination. Results: A total of 105 cases were subjected to histopathological examination. Among these, 28 cases (26.66%) were benign, 27 cases (25.71%) were malignant and 4 cases (3.80%) were pre-malignant lesions. Among the malignant lesions, SCC was most common (85.19% ), while inflammatory fibrous hyperplasia was most common among non- neoplastic lesions ( 45.65 %). Overall females were affected more than males (M: F=1: 1.1), though malignant lesions were more common in males. Malignant lesions were more common in older age group (mean age 52.26%), while non-neoplastic lesions were common in younger age group (mean age 37.87%). Malignant lesions were most common in tongue (11 cases, 40.74 %), while benign lesions were most common in gingiva (10 cases, 35.71 % ). Conclusion: A variety of benign and malignant tumors occur in oral cavity. However, the origin and nature of the oral cavity lesions cannot be confirmed by clinical examination alone. Hence, histopathological examination is essential to confirm the diagnosis and malignant potential of the oral cavity lesions.